Independence of Centers of Excellence in Medical Sciences: A qualitative study - Siamak Kazemi Asl; Azita Jaberi; Ali Reza Safarpour; Majid Reza Farrokhi; Ladan Zarshenas; Manoosh Mehrabi (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2020)
Background: Centers of excellence are organizations with prominent activities in a specific field and are capable of delivering quality services using specialized equipment, innovative techniques, and modern technologies. They can also bring financial benefits and cost recovery to their organizations. So, promoting the independence of these organizations plays a critical role in maintaining sustainable competition in their future efforts. The purpose of this study was to develop goals and challenges of independence for centers of excellence. Methods: This was a qualitative content analysis study including semi-structured interviews with 7 individuals from centers of excellence affiliated to medical sciences. Purposive sampling method was conducted and continued until data saturation was met. Interview transcripts were analyzed by coding and classifying the concepts into categories and subcategories. Later, the MaxQDA 10 software was used for further analysis. Results: According to the participants, a number of prerequisites (such as goals and strategies) are required to secure independence and authority of Iranian centers of excellence. Such independence has some distinct dimensions such as financial and human resources. Furthermore, participants identified the possible obstacles and challenges (such as: bureaucratic processes and failure to delegate authority) with regard to the independence of these centers and proposed solutions to tackle them (such as internal and external evaluations and accreditation). Conclusion: Based on the interviews and analyses, before granting independence to the scientific poles of the country, it is necessary to consider such as prerequisites, determining the desired dimensions in the independence of the poles, solving the challenges ahead and providing solutions. Also, the results can be used to set up independence regulations for policy makers to support them during the process of the independence of the poles.